Pengaruh CAR, ROE Dan NPL Terhadap Harga Saham Bank Konvensional - Aprelia Megilatul; Yudha Pratama; Rocky Gumilang (E-Journal Studia Manajemen, 2022)
This study applies certain criteria in determining the sample which is often referred to as purposive sampling. This study found 30 Conventional Banking Companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. Multiple Linear Regression is used in this study to answer the main research problem. The conclusion of this study is that the effect of CAR, ROE and NPL on stock prices is significant and positive for banking companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. Based on the results of the coefficient of determination table, the adjusted R2 value is 0.125. This means that the ability of the independent variables, namely CAR, ROE and NPL, in explaining the dependent variable, namely the stock price is 12.5%, while 87.5% is influenced by factors other than CAR, ROE and NPL which are not studied.